Motivators And Challenges of Research and Evidence-Based Practice Competency of Nursing Faculty: Basis of Research Training Framework - D. Quiros, Jejomar; Aliswag, Emerson (Journal of Neonatal Surgery, 2025)
Background: The study explores the motivators and challenges faced by nursing faculty in acquiring research and evidence-based practice (EBP) competencies, focusing on developing a research training framework. The researcher, serving as a dean in the College of Nursing within a school system, brings an administrative perspective and deep insight into the academic and professional landscape of nursing education. The background provides a unique vantage point for assessing the interplay of academic expectations, professional development, and institutional support mechanisms in fostering research culture and EBP skills. The study likely emphasizes how these factors influence faculty engagement in scholarly activities and their readiness to integrate evidence-based methods into teaching and practice. Result: The study revealed that to enhance nursing faculty’s research and evidence-based practice (EBP) competencies by addressing skills development, motivation, mentorship, and institutional support. It provides targeted training in research methodologies, promotes EBP integration through case studies and systematic reviews, and mitigates challenges like workload and resource limitations via peer mentoring. By fostering a supportive research culture through incentives, collaboration, and institutional backing, the framework strengthens faculty engagement, improves nursing education, and enhances patient outcomes. Conclusion: This study highlights the strong research and evidence-based practice (EBP) competencies among nursing faculty despite challenges such as workload, resource limitations, and mentorship gaps. It finds that research and EBP competencies are closely linked, with EBP serving as a key mediator in overcoming research challenges. However, gaps in advanced research skills, critical appraisal, and global collaboration persist, while the study’s reliance on linear models limits a deeper exploration of faculty motivations and institutional influences on competency development.